SERANGAN PENGGEREK PADI PUTIH DAN PENAMPILAN AGRONOMIS GALUR-GALUR PADI SAWAH IRIGASI - Suprapto dan Widyantoro . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2005)
The white rice borer (Tryporyza innotata Walker) attack and agronomic traits of low land paddy lines. Field trial evaluation on 10 lines/varieties to observe the white rice borer (Tryporyza innotata Walker) attack and agronomic traits was conducted at AIAT Lampung on wet season of 2004. The trial was conducted in endemic white rice borer area in Rejo Basuki, Seputih Raman District, Central Lampung. Experiment was arranged in a Randomized Block Design with four replications. Variables observed were precentage of plants attack, yield at 14% moisture contents, period of flowering, number of grain, total grain per panicle, number of stem per hill, plants height, maturity, 100 seed weight and vegetative and generative vigors. Results indicated that among the lines/varieties there were significant different on white rice borer incidence. The BP-360e-Mr-79-Pn-2 line showed low incidence of white rice borer, higher number of stem per hill height plant 104.9 cm, total grain per panicle of 5200 kg, 1000 grain weight and good on vegetative and better generative vigor. But no different seed is compared with other lines, the BP-360e-Mr-79-Pn-2 lines showed 49. 9 empty grain per panicle and 80% mature at 105 days harvested.